Screening of material libraries for electrochemical CO2 reduction catalysts - Improving selectivity of Cu by mixing with Co - Grote, Jan-Philipp; Zeradjanin, Aleksandar R.; Cherevko, Serhiy; Savan, Alan; Breitbach, Benjamin; Ludwig, Alfred; Mayrhofer, Karl (Journal of Catalysis, 2016)
The efficiency of the direct electrochemical CO2 reduction can be improved by the development of new alloy catalysts, but to do so a highly resolved composition screening remains to be connected to complex sample preparation and time consuming analysis. We have developed a technique that allows a fast and easy initial catalyst composition screening by analyzing thin film composition spread samples, utilizing a scanning flow cell coupled to an online electrochemical mass spectrometer (SFC-OLEMS). As a first case example, the investigation of a Cu-Co thin film material library demonstrates the benefits and high potential of this approach. In particular, a shift in selectivity toward C-2 species for low Co content (5-15 at.%) has been found and is discussed as being related to changed adsorption energies of intermediate products and the consequent modification of reaction pathways. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: CO2 reduction; Thin film; Ethylene; Ethanol; Alloy; Copper; Cobalt; DEMS